Notion as a Web-Based Learning Medium for Enhancing Learning Motivation in Grade VII Informatics - Ahmadah, Rasif Nidaan Khofia; Patmanthara, Syaad; Nabila, Putri Alivia; Ryanti, Rahmadita Sugma; Sa’adah, Lailatus; Kurniawan, Rachman (Journal of Innovation and Teacher Professionalism, 2026)
This study aims to examine the development of students’ learning motivation across the cycles of Classroom Action Research (CAR) through the use of Notion as an interactive learning medium in data analysis instruction. The research is motivated by the low level of student motivation observed during data analysis learning, indicating the need for appropriate solutions involving digital media, instructional methods, and effective pedagogical approaches. The study adopts a Classroom Action Research design conducted in several cycles, with data analyzed using quantitative techniques. The findings reveal that the integration of Notion as an interactive learning medium, supported by suitable teaching methods and pedagogical strategies, significantly enhances students’ learning motivation. Students demonstrate higher engagement in learning activities, increased participation during lessons, and greater interest in understanding data analysis concepts. Furthermore, Notion’s flexibility and interactive features enable systematic organization and easy access to learning materials, which further supports students’ motivation and learning autonomy. Overall, this study highlights the potential of Notion as an effective digital learning medium for enhancing students’ motivation in data analysis learning. The findings contribute to the development of innovative instructional practices and suggest that interactive digital media can be further explored and implemented in diverse learning contexts. This study may also serve as a reference for future research on technology-enhanced learning and student motivation.